"It Blew My Mind … ": Using Technology as Conduit to Teach Authentic Kenyan Music to Australian Teacher Education Students. Issue 1 (2nd January 2022) - Joseph, Dawn; Akombo, David
Abstract: In the light of critical race theory, the authors argue that by engaging in multicultural music through song, students gain cultural and historical understandings of minority groups which may break down barriers that propagate Eurocentrism in music education. In this paper we share our field experience using Zoom videoconferencing as a conduit to access and include music from Africa in initial teacher education (ITE) programmes in Australia. In their preparation to be culturally responsive, ITE students are required to participate in activities that foster understandings of other times, places, cultures, and contexts. Author One collaborated in March 2021 with Author Two, a tertiary music educator based in the United States, to teach Kenyan songs sharing about local culture, and music pedagogy to her third year Bachelor of Education (primary) generalist students in Australia. Employing narrative inquiry, we provide insights into the process of our collaboration and, through critical reflection, add insights into the context of music classroom practice. The findings show that Zoom is an effective videoconferencing platform in helping music educators collaborate to improve practice and increase students' awareness of music and people from Africa. We recommend that music educators across education settings use technology to collaborate locally and internationally with other music educators and culture bearers to promote inclusive ways of teaching and learning music from Africa. As tertiary music educators, we call on all who teach and learn to respect, recognise, and embrace diverse musical arts in their teaching and learning environments.